PERANAN EVENT F1H2O POWER BOAT DALAM MENINGKATKAN HUNIAN HOTEL DAN HOMESTAY DI BALIGE, KABUPATEN TOBA - Bantors Sihombing (Akademi Pariwisata Darma Agung, 2023)
Toba Regency is one of the areas that has a very large tourism potential. Located on the edge of Lake Toba, Toba Regency offers stunning natural beauty and rich culture. To increase the number of tourists who come to this area, the local government often holds various tourism events. One of the tourism events held in Toba Regency is the International Event F1 H2O Super Boat. This event is a speedboat racing championship that is participated by the best racers from all over the world. This championship is very popular and attended by thousands of speedboat racing fans from all over the world. That is why the writer is interested in conducting a research entitled